Pengaruh Kemandirian Terhadap Prestasi Belajar Siswa Kelas XI di SMA Negeri 11 Kota Jambi - Endah Febri Setiya Rini; Gunawan Wibisono; Auliya Ramadhanti; Nadia Natalia Simamora; Diki Chen (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aims to determine the relationship and effect of independent learning on student achievement in physics class XI MIA at SMA Negeri 11 Kota Jambi. This research uses quantitative research and the method used in this research is the survey method. The data analysis technique used the SPSS application, by performing the normality test, correlation test, and simple linear regression test. From the results of the tests that have been done, it is obtained that the Pearson correlation is 0.936 which means that it is included in the very strong correlation category. Then, based on the simple linear regression test, the regression equation Y = -52,165 + 1,283 X was obtained. From the analysis, it was found that t hit = 18,420 and t table = (0.05 / 2: nk-1) = (0.05 / 2: 50-1-1) = 2,011. From these results it can be seen that the t hit> t table, namely 18,420> 2,011. So, it can be concluded that learning independence in physics has an effect on student achievement. Based on the results of the research that has been done, it can be concluded that the independent attitude of students in learning physics has a correlation and is very influential on student achievement, especially in the cognitive aspect.